Documentation for loans, assignments and participations - Gooch, Anthony C.; Klein, Linda B.; Gooch, Anthony C.. (London : Euromoney Books, 1996)
This volume builds on the second edition, published in 1991, which introduced a sample commitment letter for a bank loan and sample loan participation and assignment agreements, together with commentary and annotations
Previous ed.: published as Loan documentation. 1991.
Includes bibliographical references and index.
osc 2/11/2021
Loans
Keywords: Loans, Foreign; Bank Loans - Law and legislation